2010
DOI: 10.1016/j.ajodo.2010.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic appliance preferences of children and adolescents

Abstract: Children's preferences for orthodontic appliances differ by age and sex. Child and adolescent preferences differ from adult preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 13 publications
7
89
1
1
Order By: Relevance
“…These data show that reduction of visible metal is not a determining esthetic factor for most children. A similar result was found in the study by Walton et al, 11 but their result was different from similar studies in adults, which found preferences for appliances with less visible metal 7 8 , 10 , 14 Group 2 gave better scores for sapphire brackets and clear aligner without attachments than Group 1, and these findings were similar to results yielded by Walton et al 11 and Oliveira et al 14 …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These data show that reduction of visible metal is not a determining esthetic factor for most children. A similar result was found in the study by Walton et al, 11 but their result was different from similar studies in adults, which found preferences for appliances with less visible metal 7 8 , 10 , 14 Group 2 gave better scores for sapphire brackets and clear aligner without attachments than Group 1, and these findings were similar to results yielded by Walton et al 11 and Oliveira et al 14 …”
Section: Discussionsupporting
confidence: 81%
“…, 8 Esthetic perception and economic value of orthodontic appliances among adults was investigated by Feu et al 10 who found that sex and age influence perception of orthodontic appliance attractiveness. Walton et al 11 found a statistically significant difference between sex and age, concluding that American adolescents have a significant preference for metallic brackets.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Esthetic wires and esthetic brackets are the principal components of esthetic labial orthodontics. Ion implantation and surface coating are two surface treatments used to improve the esthetic characteristics of an orthodontic archwire; these processes cover the metallic archwires with a superficial layer, changing their optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have concluded that clear aligners and simulated lingual appliances are the most attractive treatment modality, followed by ceramic appliances and then metal appliances [6,23]. Even older children tend to rate clear orthodontic appliances higher than younger children [24]. However, despite the increased ratings of attractiveness of ceramic brackets, attractiveness did vary with wire selection and tie variation [23].…”
Section: Orthodontic Appliances and Estheticsmentioning
confidence: 97%
“…However, despite the increased ratings of attractiveness of ceramic brackets, attractiveness did vary with wire selection and tie variation [23]. Ceramic brackets with discolored ties were rated lower in overall acceptability when compared to other esthetic appliances [24]. In 2009, Berto et al [25] examined the smile esthetics of several different versions of the same full-face photograph.…”
Section: Orthodontic Appliances and Estheticsmentioning
confidence: 99%